2019
DOI: 10.1155/2019/3089641
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Sharing Economy on Sequential Innovation Products

Abstract: The emergence of the sharing economy has affected consumers and traditional manufacturers. We focus on product sharing and analyze its impacts on the manufacturer that offers sequential innovation products. We develop a two-period model in which a monopoly manufacturer sells an old product and introduces a new product in each period; in the same period, an owner who bought a product for self-use from the manufacturer in the previous period may rent the product out because of the low self-use value in this peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 51 publications
0
17
1
Order By: Relevance
“…This is different from previous literature that concentrated mainly on the characteristics, success factors, and ways [12,23,24,43,66]. Furthermore, eight resource-constrained innovation approaches are consistent with some common understanding of resource-constrained innovation [1,8,39,67,68], and strongly support that the most promising research area for the emerging and developing countries is the frugal approach to innovation [43,61,[69][70][71].…”
Section: Discussioncontrasting
confidence: 78%
“…This is different from previous literature that concentrated mainly on the characteristics, success factors, and ways [12,23,24,43,66]. Furthermore, eight resource-constrained innovation approaches are consistent with some common understanding of resource-constrained innovation [1,8,39,67,68], and strongly support that the most promising research area for the emerging and developing countries is the frugal approach to innovation [43,61,[69][70][71].…”
Section: Discussioncontrasting
confidence: 78%
“…Tian and Jiang (2018) also found that product sharing affected the distribution channel [27]. Liu, et al (2019) examined the impact of the SE on a manufacturer's product rollover strategy [28]. Feng, et al (2019) also discussed a manufacturer's optimal business strategy involving the interaction of product sharing and product rollover in the SE [29].…”
Section: Se Pricing Strategymentioning
confidence: 99%
“…Assuming that there are two economic variables C (carbon emissions) and G (GDP), under the condition that both information are included at the same time, the prediction effect of variable C is generally better than that only using the past information of C to predict. That is, variable G helps to improve the interpretation and prediction accuracy of variable C, then it is considered that there is Granger causality between variable X and Y (Ismail et al, 2015;Mi et al, 2019;Ahmad et al, 2015;Yu et al, 2018;Liu et al, 2019;Yu et al, 2019). The twovariable autoregressive model is as follows:…”
Section: ) Granger Causality Testmentioning
confidence: 99%